2017
DOI: 10.18632/oncotarget.18191
|View full text |Cite
|
Sign up to set email alerts
|

A20 functions as mediator in TNFα-induced injury of human umbilical vein endothelial cells through TAK1-dependent MAPK/eNOS pathway

Abstract: A20, a negative regulator of nuclear factor κB signaling, has been shown to attenuate atherosclerotic events. Transforming growth factor beta-activated kinase 1 (TAK1) plays a critical role in TNFα-induced atherosclerosis via endothelial nitric oxide (NO) synthase (eNOS) uncoupling and NO reduction. In the study, we investigated the hypothesis that A20 protected endothelial cell injury induced by TNFα through modulating eNOS activity and TAK1 signalling. Human umbilical vein endothelial cells (HUVECs) were sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 31 publications
2
7
0
Order By: Relevance
“…Our data indicate that overexpression of A20 in HCAEC did not impair EC's ability to phosphorylate eNOS at Ser-1177 in response to activators such as TNF or vascular endothelial growth factor (data not shown) and even promoted this phosphorylation at baseline. This observation agrees with previous data by Li et al showing that A20 knockdown in HUVEC reduces eNOS activating phosphorylation in a TAK1/p38 MAPK-dependent manner (72). Conversely, A20 overexpression inactivates TAK1 and suppresses p38 MAPK to restore eNOS phosphorylation (72).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our data indicate that overexpression of A20 in HCAEC did not impair EC's ability to phosphorylate eNOS at Ser-1177 in response to activators such as TNF or vascular endothelial growth factor (data not shown) and even promoted this phosphorylation at baseline. This observation agrees with previous data by Li et al showing that A20 knockdown in HUVEC reduces eNOS activating phosphorylation in a TAK1/p38 MAPK-dependent manner (72). Conversely, A20 overexpression inactivates TAK1 and suppresses p38 MAPK to restore eNOS phosphorylation (72).…”
Section: Discussionsupporting
confidence: 93%
“…This observation agrees with previous data by Li et al showing that A20 knockdown in HUVEC reduces eNOS activating phosphorylation in a TAK1/p38 MAPK-dependent manner (72). Conversely, A20 overexpression inactivates TAK1 and suppresses p38 MAPK to restore eNOS phosphorylation (72). Future work is planned to investigate whether the TAK1/p38 pathway is relevant to our data in HCAEC and also to evaluate the alternative contribution of other molecular mechanisms.…”
Section: Discussionsupporting
confidence: 91%
“…One of those genes is A20 which inhibits nuclear factor κB signalling, suppresses inflammatory response and inhibits TNF‐mediated apoptosis (Hryhorowicz et al., 2017). A20 is expressed by endothelial cells as response to stress, and it is able to confer cytoprotection through downregulation of p38 MAPK and inhibition of caspase 8 activation (Daniel et al., 2004; Li et al., 2017). In order to control xenograft acute vascular rejection, researchers transferred human A20 gene sequence into the pig genome.…”
Section: Engineering Pigs For Xenotransplantationmentioning
confidence: 99%
“…A20 was also highly expressed in tamoxifen-resistant MVLN and VP (https://www.cellosaurus.org/CVCL_2755) cells, and in highly aggressive breast cancer tissues. Using its N-terminal deubiquitination function and C-terminal ubiquitination activity, A20 can negatively regulate a variety of signaling molecules in the p38MAPK/NF-κB signaling pathway, reduce the production of cellular inflammatory factors and inhibit the inflammatory response (16,17). In recent years, it has been reported that A20 is involved in the pathological progression of breast cancer.…”
Section: Introductionmentioning
confidence: 99%